1988
DOI: 10.1128/iai.56.9.2299-2306.1988
|View full text |Cite
|
Sign up to set email alerts
|

Actin-specific ADP-ribosyltransferase produced by a Clostridium difficile strain

Abstract: By screening possible ADP-ribosyltransferase activities in culture supernatants from various Clostridium species, we have found one Clostridium difficile strain (CD196) (isolated in our laboratory) that is able to produce, in addition to toxins A and B, a new ADP-ribosyltransferase that was shown to covalently modify cell actin as Clostridium botulinum C2 or Clostridium perfringens E iota toxins do. The molecular weight of the CD196 ADP-ribosyltransferase (CDT) was determined to be 43 kilodaltons, and its isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(129 citation statements)
references
References 35 publications
4
124
0
1
Order By: Relevance
“…The annual mortality attributable to CDI rose by 72% in the UK to 6500 cases in 2006 [19]. By 2005, RT 027 had been detected in an outbreak in The Netherlands [20], and by 2007 it had been isolated in 16 European countries [21,22]. The application of genotyping methods confirmed that RT 027 strains are genetically highly uniform.…”
mentioning
confidence: 90%
“…The annual mortality attributable to CDI rose by 72% in the UK to 6500 cases in 2006 [19]. By 2005, RT 027 had been detected in an outbreak in The Netherlands [20], and by 2007 it had been isolated in 16 European countries [21,22]. The application of genotyping methods confirmed that RT 027 strains are genetically highly uniform.…”
mentioning
confidence: 90%
“…The oldest variant strains in collections known to the author are isolates from 1985 (toxinotype III, IV, XXIII). Among older variant isolates is also the first binary toxin positive strain CD196 isolated in France (Popoff et al, 1988), the first known strain of type BI/NAP1/027 in Europe.…”
Section: How Old Are Toxinotypes?mentioning
confidence: 99%
“…Two families can be distinguished, the iota and C2 families . Iota family encompasses iota toxin from Clostridium perfringens type E (Stiles and Wilkins, 1986), C. spiroforme toxin (ST; Popoff and Boquet, 1988a) and C. difficile ADP-ribosyltransferase (CDT) synthesized by some strains of C. difficile (Popoff et al, 1988b;Perelle et al, 1997a;Gulke et al, 2001), while the C2 family consists of C2 toxins from C. botulinum C and D (Aktories et al, 1986;Ohishi and Tsuyama, 1986). The clostridial binary toxins are related to the vegetative insecticidal proteins produced by Bacillus cereus and B. thuringiensis, which are also actin ADPribosylating toxins, and more distantly to anthrax toxins from B. anthracis Popoff and Stiles, 2006).…”
Section: Introductionmentioning
confidence: 99%